Clinical efficiency evaluation of minimal dental restorations on occlusal teeth surfaces - Živojinović Vesna; Marković Dejan (Serbian Medical Society - Dental Section, Belgrade, 2004)
Minimal dental restoration of occlusal surfaces using sealing for prevention, preserve sound tooth structure. The aim of this study was to clinicaly assess the performance of three different techniques in minimal dental restoration. A total of 90 teeth (premolars or molars) with minimal carious lesions were equally divided into three groups and included in this study. In group I and II teeth were restored either with the composite resin and the resin modified glass ionomer cement. Composite sealant (separately applied) was used in both groups. In group III teeth received resin modified glass ionomer cement. These materials were used at the same time as a restorative and a sealant. Modified Cvar and Ryge criteria were used for clinical evaluation after 1, 2, 3, 6 and 12 months. Complete retention at the end of the evaluation period for I, II and III group was 97%, 93% and 93% respectively. No secondary caries was recorded after the evaluation period. From the obtained results it can be concluded that minimal dental restorations presents an efficient and successful technique in the treatment of small occlusal carious lesions.